Implementation of School Culture Program in Character Education Strengthening - Ariah; Widyasari (Indonesian Journal of Social Research (IJSR), 2019)
Schools have an important role in providing basic concepts to shape student personality through character education. Therefore, schools must design and manage activities that internalize character education to improve quality human resources. Strengthening Character Education (KDP) through the application of school culture is one of the efforts to develop character building in schools. The application of school culture programs in each educational institution has its own uniqueness. Among the schools that have their own unique character in the Character Building Strengthening (PPK) program are the Integrated Islamic Elementary School (SDIT) Ummul Quro Bogor. Among the characters developed by SDIT Ummul Quro are called 8 My habits, namely: 1) polite satun, 2) clean and neat, 3) prayer with awareness, 4) birrul waalidain (good to both parents), 5) discipline, 6) honest , 7) the spirit of recitations and memorization of the Koran, and 8) learners. This research was conducted aiming to analyze the implementation of school culture programs in strengthening the 8 Habku character as the development of KDP SDIT Ummul Quro. The method used is descriptive qualitative. Data obtained by observation, interview, and documentation study. The results showed that the implementation of the school culture program made a good contribution to the development of KDP students at SDIT Ummul Quro. The results of this study imply that the school culture program needs to be implemented as part of a way to shape student character.